Do Hıgh Doses Of Proteın Supplements Affect Serum Lıpıd Profıles, Bıochemıcal And Glucose Metabolısm Markers? - Cerit, levent; YÜKSEK, ÜMİT; Edebal, Oguzhan; Kemal, Hatice; Eken, Tugce Kıvılcım Bengisu; Duygu, Hamza (Progress in Nutrition, 2022)
Aim: The aim of this study was to investigate the effects of protein supplements (PS) on blood biochemical, haematological, inflammatory parameters and lipid profile. Methods: Sixty-nine healthy subjects going to the gym for at least three months were included in the study. The subjects were divided into two groups according to their PS usage status. Fasting blood samples were taken from all of the subjects. Results: Among 69 subjects, 30(43%) were using PS, so were included in group 1, and 39 (57%) never used PS, therefore they consisted of group 2. The blood biochemical, haematological, inflammatory, glucose metabolism markers and lipid profiles were not different between the two groups. But, the subjects who used > 55 g PS/day had significantly higher serum creatinine values than subjects who never used PS. Similarly, the subjects who used  ≥ 30 g PS/day had significantly higher serum sodium levels than subjects who never used PS. Moreover, the subjects using PS for more than 10 months had significantly higher serum sodium levels when compared with subjects who did not use PS. Conclusion: Blood lipid profiles were not different in subjects using PS and in subjects who never used PS and they were not related to PS dosage.